FORMULASI STRATEGI, MANAJEMEN RISIKO DAN KINERJA ORGANISASI: STUDI EMPIRIS PADA UNIT VERTIKAL DIREKTORAT JENDERAL PAJAK DI JAKARTA - Abdul Rahman (Scientax, 2022)
This study aims to analyze the effect of strategy formulation consisting of three variables, namely: strategic planning, logical incrementalism and blending approach to organizational performance with risk management effectiveness as a moderating variable at 71 Vertical Units of the Directorate General of Taxes (DGT) in Jakarta. This study uses primary data and secondary data. Primary data were obtained from distributing questionnaires to measure variables related to strategy formulation, while secondary data were used to measure the variables of risk management effectiveness and organizational performance. The data obtained were analyzed with the help of SPSS 22 and WarpPLS 5.0 applications. Based on the results of the analysis, it was concluded that two variables related to strategy formulation, namely strategic planning and blending approach, had a significant positive effect on organizational performance, while the other variable, that is logical incrementalism, had a significant negative effect on organizational performance. In addition, the effectiveness of risk management does not significantly affect the relationship between strategic planning, logical incrementalism and blending approach to organizational performance.